2001
DOI: 10.1051/0004-6361:20000261
|View full text |Cite
|
Sign up to set email alerts
|

Can the gamma-ray source 3EG J2033+4118 be produced by the stellar system Cygnus OB2 No. 5?

Abstract: Abstract. We discuss the possibility that the stellar system Cyg OB2 No. 5 can be a gamma-ray source in the light of recent EGRET and radio data. This system is formed by an O7 Ia + Ofpe/WN9 contact binary. A third star, probably a B0 V star also associated with the system, is located at ∼1700 AU from the primary. We estimate the expected gamma-ray luminosity from the colliding winds region, the terminal shock of the wind, and the unstable zone at the base of the wind, and conclude that, under very reasonable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 38 publications
(49 reference statements)
0
70
0
Order By: Relevance
“…A surface magnetic field of ∼ 100 G would give a L IC a factor 10 4 lower. For comparison, Benaglia et al (2001) derive a value of about 8 × 10 34 erg s −1 for Cyg OB2 #5. We also estimated the maximum energy that can be reached by the relativistic electrons under these conditions, using the relation given by Benaglia & Romero (2003).…”
Section: Cyg Ob2 #8a In the Context Of This Scenariomentioning
confidence: 98%
“…A surface magnetic field of ∼ 100 G would give a L IC a factor 10 4 lower. For comparison, Benaglia et al (2001) derive a value of about 8 × 10 34 erg s −1 for Cyg OB2 #5. We also estimated the maximum energy that can be reached by the relativistic electrons under these conditions, using the relation given by Benaglia & Romero (2003).…”
Section: Cyg Ob2 #8a In the Context Of This Scenariomentioning
confidence: 98%
“…Romero et al (1999) found a significant correlation (at the 4 σ level) of unidentified EGRET sources with OB associations. Their study further provides evidence that several individual massive binaries, including WR 140 and the multiple system V 729 Cyg, are probable counterparts of γ-ray sources (see also Chen et al 1996;Benaglia et al 2001). …”
Section: Predictions For the γ-Ray Domainmentioning
confidence: 89%
“…Because of the strong UV radiation field of luminous early-type stars, relativistic electrons are expected to dissipate most of their energy through the inverse-Compton scattering mechanism (Mücke & Pohl 2001) and the expected luminosities are of the order of a few times 10 34 erg s −1 (Benaglia et al 2001). …”
Section: Predictions For the γ-Ray Domainmentioning
confidence: 99%
“…The clear detection of non-thermal radio emission from the colliding wind region in some systems like WR140, WR146, WR 147, and Cyg OB2 #5 indicate that electrons are been accelerated up to relativistic energies in these binaries. These electrons are located relatively close to the secondary star, so they should have strong inverse Compton losses which might result in a detectable gamma-ray signal [32,33]. Protons can be in principle also accelerate in the colliding wind shock and they can interact either with the wind material [34] or they can diffuse to interact with nearby molecular clouds [35].…”
Section: Gamma Rays From Massive Stars and Massive Binary Systemsmentioning
confidence: 99%